Pemanasan Global, Faktor Penyebab, Dampak dan Solusi - ., Fadliah (Jurnal Pelangi Ilmu, 2008)
The root cause global warm-up be annoyed the balance of nature as result of act of man, that is increasingly carbon gas thickness (C02) blankets earth causing increases Gas Rumah Kaca. Forest is one of important resource, not only in supporting economics, but also in taking care of environmental carrying capacity to balance of world ecosystem. Resource involves with all the varieties having big role in guarantying civilization continuity of something nation. Therefore needs existence of straightening of law related to environment problem covers criminal law aspect, civil, arranges effort for state and international law.